Pathomorphologic investigations on the genital system of ewes I. Ovarium and oviduct - Karadas, E; Timurkaan, N (Scientific Technical Research Council Turkey, 1999)
This study was carried out to determine the pathomorphologic changes and the incidence of these changes in the ovarium. oviduct and related ligaments of ewes slaughtered in Elazig abattoirs. For this purpose, the genital organs of 6100 ewes of different breeds and ages were examined. There were pathomorphologic changes in 302 cases (4.95%) in ovaries and 106 cases (1.73%) in oviducts. These changes in and around ovaries were parovarian cysts (2.41%), corpus luteum cysts (0.85%), follicular cysts (0.62%), luteal cysts (0.27%), tuboovarian cysts (0.06%), oophoritis (0.16%), periovaritis-adhesions (0.50%) and ovarian hypoplasia (0.21%). in the oviducts, salpingitis (0.62%), mesosalpingitis-adhesions (0.60%), hydrosalpinx (0.40%), pyosalpinx (0.21%) and melanosis (0.19%) were recorded.
Keywords: ewe; ovarium; oviduct; pathomorphology